Design and simulation of a single cylinder high speed spark ignition linear engine with spring system - Aguk Zuhdi, Muhammad Fathallah (2011)
This thesis deals with the design of a single cylinder high-speed spark ignition linear engine with a spring system return cycle. The main objective of the research is to design and analyse a free piston linear engine that is easy to start, easy to maintain and easy to control. The unique design of the spring as a return cycle in a free piston linear engine is presented and its effects on engine performance and motion are discussed. The engine performance has been predicted the aim is to design a linear engine particularly for the spring system. The spring design has been optimised by using a multilevel optimization approach. Based on the optimisation of the spring design, the linear engine geometry design has been conducted. The performance of the linear engine design has been measured and the results compared with the predicted performance. Besides which the motion of the linear engine has been studied; however, friction affect show the rotated of the piston. It is necessary to modify the spring mechanism to ensure that the scavenging process works properly. Two scenarios such as the removal of the bottom part of the piston skirt and adding a lock to the connecting rod are recommended, based of structural stress and thermal-structural stress analysis. Software has been used in the research to analyse the design of the free piston linear engine with a spring system, including GT-Power, SolidWorks, Matlab, Algor, and Spread-Sheet. The model has been built using GT-Power to predict the engine performance. To validate the model, it has been assessed with the original engine manual and experimentally. Three step multilevel optimisation of the spring geometry has been carried out by using Matlab and Spread-Sheet. SolidWorks has been used to design all of the components and for the assembly of the linear engine. Cosmos motion, which is a part of the SolidWorks facility, has been used to analyse the piston dynamics of the linear engine. Once again, GT-Power has been used to analyse the effect of the spring design on the linear engine performance. For the modification of the design of the spring system, Algor has been used to analyse the thermal-structural stress of the piston and the connecting rod. Through step by step considerations started from building model to predict the performance of linear engine, to optimize the spring geometry design then continued build the free piston linear engine with spring system including design, analyses and modified. The result is a design which predicts the performance and the dynamics of piston motion. Only 50% of the 12 speeds sampled worked correctly. The rotation of the piston on the Z-ordinate can be fixed through modification of the piston or connecting rod. A design of a single cylinder high-speed spark ignition linear engine with spring system as return cycle has been carried out. Although the range of speeds was narrow compared to a conventional engine, the maximum power output is still higher. The final design result was 1.03 kW at 3.6 m/sec.